Retention of medical graduates from rural compulsory services program in primary care: An eight-year follow-up study based on four colleges - Zheng Huixian; Tang Haoqing; Li Mingyue; Tian Yiran; Han Leyang; Long Ren; Liu Xiaoyun (Chinese General Practice Journal, 2025)
Background: The training of Compulsory Services Program (CSP) graduates is an important initiative to alleviate the shortage of medical human resources in rural areas. As of October 2023，three batches of CSP graduates have completed their required service obligations. However，there is still a lack of systematic research and definitive conclusions regarding their career development and whether they will continue to serve in rural areas after fulfilling their service commitments. Objective: Based on eight years of panel data from a cohort of CSP graduates，this study aims to analyze their early career development characteristics and identify key factors influencing their retention in primary healthcare settings. The findings are intended to provide policy recommendations for the training and management of CSP graduates in China. Methods: Since 2010，a dynamic follow-up cohort has been established，involving CSP graduates from Qinghai University，Guangxi Medical University，Jiujiang University，and Gannan Medical University. This study utilized data from 2 041 graduates from the 2015-2019 cohorts，collected through annual online surveys conducted over eight years. The surveys tracked their career development，including professional title promotion，administrative role acquisition，average monthly income，and the proportion of performance-based pay. Descriptive analysis was used to summarize the characteristics of career development，while Logistic regression models were employed to explore factors influencing retention in primary healthcare settings after the contractual period. Results: Among the 2 041 CSP graduates included，1 068（52.3%）were male and 973（47.7%）were female. By the eighth year after graduation，92.0%（69/75）of graduates had obtained the title of attending physician，and 24.0%（18/75）held administrative positions. The average monthly income was 5 573.4 yuan，with performance-based pay accounting for 45.7% of the total. As of December 2023，with 232 graduates remaining in their positions after contract completion，resulting in a 37.5% retention rate in primary healthcare settings. Among the 386 graduates who left primary healthcare settings，136（35.2%）transitioned to hospitals above the county level，representing the largest proportion，followed by 107（27.7%）moving to county-level hospitals，and 29.0（7.5%）pursuing graduate studies. Multivariate Logistic regression analysis revealed that contract placement in home county/city（OR=2.74，95%CI=1.57-4.78，P=0.001）and holding administrative positions（OR=2.02，95%CI=1.14-3.59，P=0.016）were significant facilitators of retention in primary healthcare settings post-contract completion among CSP graduates. Conversely，passing the national medical licensing exam within two years of graduation（OR=0.37，95%CI=0.15-0.94，P=0.036）emerged as a barrier to retention. Conclusion: CSP graduates show rapid career progression，with over half choosing to remain in county-level or lower primary healthcare settings after fulfilling their contracts. This strengthens human resource capacity and improves care quality in primary healthcare settings. Notably，CSP graduates who obtained physician qualification within two years post-graduation exhibited significantly higher occupational mobility in primary healthcare settings.